2016
DOI: 10.1051/0004-6361/201526719
|View full text |Cite
|
Sign up to set email alerts
|

Weak-lensing-inferred scaling relations of galaxy clusters in the RCS2: mass-richness, mass-concentration, mass-bias, and more

Abstract: We study a sample of ∼10 4 galaxy clusters in the redshift range 0.2 < z < 0.8 with masses M 200 > 5 × 10 13 h −1 70 M , discovered in the second Red-sequence Cluster Survey (RCS2). The depth and excellent image quality of the RCS2 enabled us to detect the cluster-mass cross-correlation up to z ∼ 0.7. To obtain cluster masses, concentrations, and halo biases, we fit a cluster halo model simultaneously to the lensing signal and to the projected density profile of red-sequence cluster members, because the latter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 127 publications
(215 reference statements)
6
42
1
Order By: Relevance
“…Our own analysis of weak lensing data for a subset of the clusters used in this work finds an ensemble average concentration of 3.0 +4.4 −1.8 (Paper IV), consistent with our X-ray results here within the statistical uncertainties. Results using strong and weak lensing by X-ray selected clusters (Okabe et al 2013) and from stacked analyses of optically selected clusters (Mandelbaum et al 2008;Du et al 2015;Shan et al 2015;van Uitert et al 2016) are in broadly good agreement with our results. However, an arguably better comparison is with the lensing analyses of the CLASH sample of clusters (0.19 < z < 0.89), which mostly consists of relaxed or nearly relaxed clusters (by our definition).…”
Section: Nfw Concentration-mass Relationsupporting
confidence: 90%
“…Our own analysis of weak lensing data for a subset of the clusters used in this work finds an ensemble average concentration of 3.0 +4.4 −1.8 (Paper IV), consistent with our X-ray results here within the statistical uncertainties. Results using strong and weak lensing by X-ray selected clusters (Okabe et al 2013) and from stacked analyses of optically selected clusters (Mandelbaum et al 2008;Du et al 2015;Shan et al 2015;van Uitert et al 2016) are in broadly good agreement with our results. However, an arguably better comparison is with the lensing analyses of the CLASH sample of clusters (0.19 < z < 0.89), which mostly consists of relaxed or nearly relaxed clusters (by our definition).…”
Section: Nfw Concentration-mass Relationsupporting
confidence: 90%
“…This miscentering effect is important for applications of optically-selected clusters such as weak lensing analysis. Miscentering of optically-selected clusters have indeed been studied with various approaches, including offsets between optical and X-ray cluster centers (e.g., Lin et al 2004;Mahdavi et al 2013;Oguri 2014;Rykoff et al 2016), offsets between optical and SZ cluster centers (e.g., Song et al 2012;Sehgal et al 2013;Sifón et al 2013;Saro et al 2015), and weak lensing (e.g., Oguri et al 2010;George et al 2012;Oguri 2014;Ford et al 2014;Viola et al 2015;van Uitert et al 2016;Miyatake et al 2016). In this paper we use offsets between HSC Wide S16A clusters, whose centers are defined by the locations of BCGs identified by the CAMIRA algorithm (see Oguri 2014), and the X-ray clusters from XXL and XMM-LSS to study the miscentering effect.…”
Section: Positional Offset Distributionmentioning
confidence: 99%
“…Such surveys will also provide some statistical weak lensing constraints for clusters out to z ∼ 1 (e.g. van Uitert et al 2016), but it still needs to be demonstrated how reliably such measurements can be conducted from the ground as most of the distant background galaxies are poorly resolved. At such cluster redshifts HST is currently unique with its capabilities to measure robust individual cluster masses with good signal-to-noise ratio.…”
Section: C O N C L U S I O N Smentioning
confidence: 99%
“…High et al 2012;Israel et al 2012;Oguri et al 2012;Applegate et al 2014;Gruen et al 2014;Umetsu et al 2014;Ford et al 2015;Hoekstra et al 2015;Kettula et al 2015;Battaglia et al 2016;Lieu et al 2016;van Uitert et al 2016;Melchior et al 2017;Simet et al 2017). To constrain the evolution of cluster mass-observable scaling relations, these measurements need to be complemented with constraints for higher redshift clusters.…”
Section: Introductionmentioning
confidence: 99%